1993
DOI: 10.1093/jac/31.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of genes encoding erythromycin ribosomal methylases and an erythromycin efflux pump in epidemiologically distinct groups of staphylococci

Abstract: Erythromycin-resistant staphylococci can be divided into two phenotypic classes based on their pattern of cross-resistance to other macrolides, lincosamides and type B streptogramins. Strains inducibly or constitutively resistant to all MLS antibiotics possess erythromycin ribosomal methylase (erm) genes, whereas strains inducibly resistant to only 14 and 15-membered ring macrolides and type B streptogramins harbour msrA, which encodes an ATP-dependent efflux pump. Dot-blot hybridization was used to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
112
3
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(141 citation statements)
references
References 0 publications
22
112
3
4
Order By: Relevance
“…Target modification is the most widespread resistance mechanism and refers to the dimethylation of an adenine residue in the 23S rRNA. Four rRNA methylase (erm) genes, designated erm(A), erm(B), erm(C), and erm(F), have until now been identified in staphylococci of animal origin [14,20,27,38,39,73,85,90,103,104,106].…”
Section: Resistance To Macrolides Lincosamides and Streptograminsmentioning
confidence: 99%
See 4 more Smart Citations
“…Target modification is the most widespread resistance mechanism and refers to the dimethylation of an adenine residue in the 23S rRNA. Four rRNA methylase (erm) genes, designated erm(A), erm(B), erm(C), and erm(F), have until now been identified in staphylococci of animal origin [14,20,27,38,39,73,85,90,103,104,106].…”
Section: Resistance To Macrolides Lincosamides and Streptograminsmentioning
confidence: 99%
“…Studies of the occurrence of the different erm genes among animal staphylococci [14,20,27] showed that erm(C) genes were frequently seen in S. hyicus and other porcine staphylococci [20,27], but also in many staphylococcal species from various animal sources [38,39,73,85,90,106] while erm(B) genes were the dominant erm genes in canine S. intermedius isolates [8,20]. Genes of the class erm(F) have so far only been detected in a few S. intermedius iso-lates from pigeons [14] and erm(A) genes have also only been identified in single animal staphylococcal isolates, mainly of avian origin [47,103] and porcine origin [27].…”
Section: Resistance To Macrolides Lincosamides and Streptograminsmentioning
confidence: 99%
See 3 more Smart Citations